2014
DOI: 10.1007/s12017-014-8305-y
|View full text |Cite
|
Sign up to set email alerts
|

miR-145 Inhibits Migration and Invasion of Glioma Stem Cells by Targeting ABCG2

Abstract: Despite advances in clinical therapies and technologies, the prognosis for patients with malignant glioma is poor. Our previous research demonstrated that glioma stem cells (GSCs) were crucial for glioma malignancy and accelerated tumor migration and invasion. The migration and invasion of malignant glioma cells into the surrounding normal brain tissues cause the poor outcome. miR-145, a miRNA found to be expressed in neurons, was recently found to have reduced expression in glioblastoma multiforme tumors. And… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 33 publications
3
44
1
Order By: Relevance
“…It has been well established that microRNAs (miRNAs) are a large group of post-transcriptional gene regulators that potentially play essential roles in multiple biological processes, including cell differentiation, proliferation, angiogenesis, invasion and migration (Bartel, 2004;Esquela-Kerscher and Slack, 2006;Shi et al, 2014;Zhong et al, 2014). Recently, deregulation of miRNAs in cancer cells and their roles in tumorigenesis have been increasingly investigated (Calin and Croce, 2006;Esquela-Kerscher and Slack, 2006;Rico-Rosillo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that microRNAs (miRNAs) are a large group of post-transcriptional gene regulators that potentially play essential roles in multiple biological processes, including cell differentiation, proliferation, angiogenesis, invasion and migration (Bartel, 2004;Esquela-Kerscher and Slack, 2006;Shi et al, 2014;Zhong et al, 2014). Recently, deregulation of miRNAs in cancer cells and their roles in tumorigenesis have been increasingly investigated (Calin and Croce, 2006;Esquela-Kerscher and Slack, 2006;Rico-Rosillo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have revealed that miRNAs regulate the behavior of GSCs and may have similar functions to oncogenes or tumor suppressors [4]. For example, miR-20a and miR-106a enhance the invasiveness of GSCs [5], whereas miR-145 inhibits the migration and invasion of GSCs [6]. MiR-29a belongs to the miR-29 family, which consists of miR-29a, -29b and -29c.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ADAM17, NEDD9, and ROCK1 have been identified as target genes by which miR-145 exerts antitumoral effect [19][20][21]. On the other hand, miR-145 appears to regulate OCT4, SOX2, and KLF4, the pluripotency factors of human stem cells, inhibited migration, invasion, and self-renewal of glioma stem cells [22][23][24]. Based on these reported activities of miR145, we hypothesized that miR-145 mimic might enhance the antitumoral activity of Sunitinib.…”
Section: Introductionmentioning
confidence: 99%